An Up‐to‐Date Review on Alginate Nanoparticles and Nanofibers for Biomedical and Pharmaceutical Applications. Issue 22 (23rd October 2021) - Dodero, Andrea; Alberti, Stefano; Gaggero, Giulia; Ferretti, Maurizio; Botter, Rodolfo; Vicini, Silvia; Castellano, Maila
Abstract: Alginate is a naturally occurring polysaccharide commonly derived from brown algae cell walls which possesses unique features that make it extremely promising for several biomedical and pharmaceutical purposes. Alginate biomaterials are indeed nowadays gaining increasing interest in drug delivery and tissue engineering applications owing to their intrinsic biocompatibility, non‐toxicity, versatility, low cost, and ease of functionalization. Specifically, alginate‐based nanostructures show enhanced capabilities with respect to alginate bulk materials in the targeted delivery of drugs and chemotherapies, as well as in helping tissue reparation and regeneration. Hence, it is not surprising that the number of scientific reports related to this topic have rapidly grown in the last decade. With these premises, the present review aims to provide a comprehensive state‐of‐the‐art of the most recent advances in the preparation of alginate‐based nanoparticles and electrospun nanofibers for drug delivery, cancer therapy, and tissue engineering purposes. After a short introduction concerning the general properties and uses of alginate and the concept of nanotechnology, the recent literature is then critically presented to highlight the main advantages of alginate‐based nanostructures. Finally, the current limitations and the future perspectives and objectives are discussed in detail. Abstract : Alginate nanomaterials hold great promises in the biomedical and pharmaceutical industry owing to their biocompatibility, versatility, easy fabrication, and "smart" properties. Among others, in recent years alginate nanoparticles and alginate electrospun nanofibers have gained an increasing interest in drug delivery, cancer therapy, and tissue engineering.